Growth of Coastal Population: Likely Exposure to Sea Level Rise and Associated Storm Surge Flooding in the Sultanate of Oman - AL-AWADHI, Talal; RAMADAN, E.; CHOUDRI, B.S.; CHARABI, Yassine (Journal of Environmental Management and Tourism, 2016)
Coastal zones are densely populated than the hinterland and exhibit higher rates of population growth and urbanization. As this trend is expected to continue into the future in the case of Oman as well since more population is living the along coast. On the other hand, this population has likely exposure to coastal hazards including sea-level rise and associated storm surge flooding effects. This study investigated extent of inundation to sea level rise and built up areas exposure to possible storm surge flooding cross governorates at different scenarios. Use of remote sensing data and GIS applications employed for the assessments. Results show that the coastal area of the Governorates of Al- Wusta and South Al Sharquiya will be highly exposed to the most likely tropical cyclones since these areas are characterized by a flat topography. Further, the results of assessment show that Oman is highly vulnerable to climate change-induced sea level rise (SLR). At the national scale, nearly 400 square kilometer of total land area is projected to be inundated under the smallest SLR scenario. Overall, the assessment results highlight that Oman is vulnerable to coastal flooding and SLR therefore policies and adaptive planning for building resilient coastal communities are essential for the future.
Keywords: risk assessment; climate change; sea level rise; flooding hazard; Oman